Since she went away ebook - Bell, David (2016)
From the USA Today bestselling author of Kill All Your Darlings comes a chilling novel of guilt, regret, and a past that refuses to die....   Three months ago, Jenna Barton was supposed to meet her lifelong best friend Celia. But when Jenna arrived late, she found that Celia had disappeared—and she hasn’t been seen since.    The only piece of evidence is a lone diamond earring found where Celia and Jenna were planning to meet, leading the national media to dub Celia “The Diamond Mom.” And even though Jenna has obsessively surfed message boards devoted to missing persons cases, she is no closer to finding any answers—or easing her guilt.   But when her son’s new girlfriend disappears too, a stricken Jenna begins to unwind the tangled truth behind Celia’s tragedy. And as long-buried secrets finally come to light, she discovers how completely lives can be shattered by a few simple lies.